2011
DOI: 10.1002/jcb.23007
|View full text |Cite
|
Sign up to set email alerts
|

Icariin is more potent than genistein in promoting osteoblast differentiation and mineralization in vitro

Abstract: There has been a strong interest in searching for natural therapies for osteoporosis. Genistein, an isoflavone abundant in soy, and icariin, a prenylated flavonol glycoside isolated from Epimedium Herb, have both been identified to exert beneficial effects in preventing postmenopausal bone loss. However, the relative potency in osteogenesis between the individual phytoestrogen flavonoids remains unknown. The present study compared ability of genistein and icariin in enhancing differentiation and mineralization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(102 citation statements)
references
References 29 publications
(32 reference statements)
5
96
0
Order By: Relevance
“…Using chlorpromazine to block clathrin and genistein or nystatin to block caveolin-mediated uptake, we could clearly identify clathrin-mediated endocytosis as the major route of BMP2 internalization. Genistein reduced BMP2 internalization at later time points, which could be explained by complementary routes of clathrin-and caveolinmediated endocytosis, as suggested in the model of Hartung et al (Hartung et al, 2006), but may be better explained by other mechanisms resulting from inhibition of tyrosine kinases by genistein (Aoki et al, 1999;Sharma et al, 2004;Ma et al, 2011). In fact, nystatin, which is also commonly used to block caveolinmediated internalization (Rothberg et al, 1992;Di Guglielmo et al, 2003;Chen, 2009), did not inhibit BMP2 uptake.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Using chlorpromazine to block clathrin and genistein or nystatin to block caveolin-mediated uptake, we could clearly identify clathrin-mediated endocytosis as the major route of BMP2 internalization. Genistein reduced BMP2 internalization at later time points, which could be explained by complementary routes of clathrin-and caveolinmediated endocytosis, as suggested in the model of Hartung et al (Hartung et al, 2006), but may be better explained by other mechanisms resulting from inhibition of tyrosine kinases by genistein (Aoki et al, 1999;Sharma et al, 2004;Ma et al, 2011). In fact, nystatin, which is also commonly used to block caveolinmediated internalization (Rothberg et al, 1992;Di Guglielmo et al, 2003;Chen, 2009), did not inhibit BMP2 uptake.…”
Section: Discussionmentioning
confidence: 89%
“…8A). Chlorpromazine reduced FL-BMP2 uptake at all time points, to a lesser extent at 3 h and more clearly after 6 and 12 h. Upon treatment with genistein, reduced uptake was only clearly visible after 12 h. At this time point the inhibition of uptake by genistein could be a secondary effect not related to caveolin-mediated internalization but rather result from the tyrosine kinase inhibitor activity of genistein (Aoki et al, 1999;Ma et al, 2011). Co-incubation with both inhibitors showed an additive effect on FL-BMP2 internalization at the 12 h time point, indicating complementary activity after this extended incubation (Fig.…”
Section: Bmp2 Is Internalized Through a Clathrin-dependent Mechanismmentioning
confidence: 84%
See 1 more Smart Citation
“…Total flavones of Epimedium (TFE) inhibited reduction of procollagen type I N-terminal propeptide (PINP), and increased serum osteocalcin and type I collagen in OVX rats (13,14). Icariin, one of the major components of Herba Epimedium, decreased activities of serum tartrate-resistant acid phosphatase (TRAP) and bioactive components could stimulate the proliferation, differentiation and mineralization of osteoblasts (12,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), suppress the adipogenesis of bone marrow-derived mesenchymal stem cells (BMSCs) (41)(42)(43)(44), inhibit the proliferation and differentiation of osteoclasts (45)(46)(47), and induce apoptosis and cell cycle arrest and suppress bone resorption of osteoclasts (48). In addition, icariin was found to significantly attenuate oxidative stress and apoptosis and preserve viability and osteogenic potential of osteoblasts exposed to hypoxia, which indicated that its anti-osteoporotic effect might be attributed to its anti-hypoxic activity (49).…”
Section: In Vivo Findingsmentioning
confidence: 99%
“…Prenylated flavonoids generally showed greater binding energies than those of the non-prenylated flavonoids. It was concluded that the prenylated flavonoids from Lonchocarpus possibly owe the cytotoxic activity by suppressing the activity of some enzymes: aromatase (CYP 19), fatty acid synthase (FAS), xanthine oxidase (XO), cyclooxygenases (COX-1 and COX-2), lipoxygenase (LOX-3), ornithine decarboxylase (ODC), protein tyrosine kinase (PTK), phosphoinositide 3-kinase (PI3K), protein kinase C (PKC), topoisomerase II (ATP-binding site), ATPbinding cassette (ABC) transporter and phospholipase A(2) (PLA) (Ma et al, 2011).…”
Section: Enzyme Inhibitor and Enhancermentioning
confidence: 99%